Descriptive analysis of routine childhood immunisation timeliness in the Western Cape, South Africa. (April 2022) - Blose, Ntombifuthi; Amponsah-Dacosta, Edina; Kagina, Benjamin M.; Muloiwa, Rudzani
Highlights: Immunisation coverage has an inverse relationship with age, while delay in vaccine uptake has a direct relationship with age. High vaccine coverage rates do not translate to timely receipt of routine childhood vaccines. Time-at-risk for vaccine preventable diseases is positively associated with increasing immunisation age timepoints. Preschool attendance and having adult caregivers are protective against delaying vaccine uptake. Low and upper-middle socio-economic quartiles are associated with delayed uptake of routine childhood vaccines. Abstract: Adherence to recommended age-specific immunisation schedules is critical in ensuring vaccine effectiveness against vaccine preventable diseases (VPDs). There is limited data on immunisation timeliness in sub-Saharan Africa. Therefore, this study assessed the timeliness of age-specific routine childhood immunisation within the Western Cape Province of South Africa. Participant records (N = 709) from a prospective health-facility based study conducted in Cape Town, SA in 2012–2016 were analysed. The outcome measure was receiving age-specific immunisations ≥4 weeks of that recommended for age as per the South African Expanded Programme on Immunisation (EPI-SA) schedule. Proportions, medians, inter-quartile ranges (IQR) and regression were used to obtain the prevalence, time-at-risk, and risk factors for delayed immunisation. A total of 652 /709 (91.9%) participants were eligible. Immunisation coverage declined with age from 94.9% (95% CI 92.9–96.4) at birth to 72.0% (95% CI 65.7–77.6) at 18 months. The highest delay in the uptake of vaccine doses was observed among the 3 rd dose of the DTP vaccine [163 (34.6% (95% CI 30.3–39.1)], while the lowest was seen among BCG [40 (6.5% (95% CI 4.7–8.8)]. The longest median time-at-risk of VPDs was among the 2 nd dose of the measles vaccine [12.9 (IQR 6.7–38.6) weeks] and the lowest was OPV birth dose [IQR 6.3 (5.3–9.1) weeks]. Low and upper-middle socio-economic quartiles were associated with delayed uptake of vaccine doses. Delayed vaccination increases the time of susceptibility to VPDs during infancy and childhood. There is a need to develop strategies aimed at mitigating factors associated with delay in uptake of routine childhood vaccines in the Western Cape. Mitigation strategies should provide vaccine education and mobile reminder systems. Education about timely vaccine uptake will aid in the provision of informed council from healthcare providers to caregivers. Multiple reminder systems could cater for low network coverage areas and caregivers with busy schedules.